2020
DOI: 10.1094/phyto-02-20-0029-r
|View full text |Cite
|
Sign up to set email alerts
|

Refining the Life Cycle ofPlasmodiophora brassicae

Abstract: As a soilborne protist pathogen, Plasmodiophora brassicae causes the devastating clubroot disease on Brassicaeae crops worldwide. Due to its intracellular obligate biotrophic nature, the life cycle of P. brassicae is still not fully understood. Here, we used fluorescent probe-based confocal microscopy and transmission electron microscopy (TEM) to investigate the infection process of P. brassicae on the susceptible host Arabidopsis under controlled conditions. We found that P. brassicae can initiate the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 31 publications
4
87
0
Order By: Relevance
“…structures of P. brassicae and visualize the pathogen under confocal microscope examination (Liu et al, 2020). We firstly used the live cells HLG and DAPI to label and visualize P. brassicae at 2 dpi and found that several lipid droplet-enriched uninucleate primary plasmodia were always detected in an single root epidermal cell of resistant host B. napus ECD10, comparable to the susceptible host B. napus Westar (Figure 2A), indicating a successful initiation of the primary infection in resistant hosts.…”
Section: Identifying Clubroot-resistant Germplasm From European Clubrmentioning
confidence: 97%
See 4 more Smart Citations
“…structures of P. brassicae and visualize the pathogen under confocal microscope examination (Liu et al, 2020). We firstly used the live cells HLG and DAPI to label and visualize P. brassicae at 2 dpi and found that several lipid droplet-enriched uninucleate primary plasmodia were always detected in an single root epidermal cell of resistant host B. napus ECD10, comparable to the susceptible host B. napus Westar (Figure 2A), indicating a successful initiation of the primary infection in resistant hosts.…”
Section: Identifying Clubroot-resistant Germplasm From European Clubrmentioning
confidence: 97%
“…The isolate of P. brassicae used in this study is from the diseased canola plants in the field (Edmonton, Alberta, Canada). Maintenance of P. brassicae, resting spore preparation, and inoculation were performed as previously described (Liu et al, 2020). Ten-day-old seedlings were inoculated with 1 ml resting spore suspension (1.0 × 10 8 spores/ml) of the P. brassicae isolate.…”
Section: Plant Growth and Pathogen Inoculummentioning
confidence: 99%
See 3 more Smart Citations